Structure of finite nondispersible groups each nonmetacyclic subgroup of which is normal - Kovalenko, V. I.; Коваленко, В. І. (Institute of Mathematics, NAS of Ukraine, 1996)
We determine the structure of finite minimal nondispersible groups each nonmetacyclic subgroup of which is normal (Theorem 2) and describe all finite nondispersible groups each nonmetacyclic subgroup of which is normal (Theorem 3).